2015
DOI: 10.1002/pen.24253
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of multilayer foamed composite by rotational molding

Abstract: A multilayer material was produced by rotational molding to study the effect of composition on the mechanical behavior of a cylindrical liquid container. The first (outer) layer was a composite of linear medium density polyethylene (LMDPE) with 5, 10, or 15 wt% agave fiber (AF). The core (middle) layer was foamed LMDPE with different amount of foaming agent (0, 0.15, 0.25, 0.5, and 0.75 wt%). Finally, the third (internal) layer was neat LMDPE. This structure was produced to optimize the mechanical properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Finally, the fibers were grounded and sieved to keep only the fibers between 100 mesh and 140 mesh to give and average size between 106 and 150 microns. This particle size produced the best dispersion, distribution and mechanical performance, according to previous studies [16,23]. Before rotational molding, the fibers were dried again in an oven for 24 h at 60 • C to reach moisture contents less than 1%.…”
Section: Fiber Preparationmentioning
confidence: 81%
See 4 more Smart Citations
“…Finally, the fibers were grounded and sieved to keep only the fibers between 100 mesh and 140 mesh to give and average size between 106 and 150 microns. This particle size produced the best dispersion, distribution and mechanical performance, according to previous studies [16,23]. Before rotational molding, the fibers were dried again in an oven for 24 h at 60 • C to reach moisture contents less than 1%.…”
Section: Fiber Preparationmentioning
confidence: 81%
“…The addition of 0.75% ACA resulted in 103%, 108% and 127% thickness increase when using 5%, 10% and 15% of AF, respectively. In a previous work [23], it was shown that at low proportions (<15 wt %), fiber addition generally does not affect the total thickness of rotomolded parts.…”
Section: Morphologymentioning
confidence: 89%
See 3 more Smart Citations